Proposed Social Media Marketing Strategy To Increase Social Media Engagement For Teknisigo - Gianluca Biata Malau (Riviera Publishing, 2025)
This study addresses the gap between current content delivery and audience expectations on Teknisigo's Instagram, a challenge often overlooked in service-based SMEs. Despite the widespread use of social media marketing, limited research explores how different content types influence user engagement in niche service industries. This research aims to develop an improved content strategy by identifying which content types drive the highest engagement. The study applies an internal STP (Segmentation, Targeting, Positioning) analysis to understand the audience profile, followed by external benchmarking with similar businesses. A mixed-methods approach was used, combining thematic interviews with internal stakeholders and an online survey of followers to assess preferences, motivations, and content satisfaction. Quantitative data were analyzed using Spearman’s rank correlation to identify relationships between content types and engagement. The findings reveal a significant mismatch between audience expectations and Teknisigo’s current content. Educational and relational content—such as tutorials, customer stories, and behind-the-scenes features—proved more engaging than promotional or entertainment-based posts. As a result, a revised content strategy is proposed to focus on high-performing content categories. This research offers practical recommendations for Teknisigo and provides a replicable content planning framework for service-based SMEs seeking to improve social media engagement.